Carbon stock determination of selected terrestrial ecosystem in the Upper Marikina Watershed, Antipolo City, Rizal Province, Philippines - Almarines, Nico R. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2014)
Ecosystem play a vital role in the issue of climate change because these serve as carbon sinks through the process of photosynthesis. In this study, the biomass and carbon stock in the carbon pools of some terrestrial ecosystems in the Upper Marikina Watershed were assessed through a system of efficient, cost-effective methods of field and laboratory measurements; thus generating much needed baseline carbon stock data of the Upper Marikina Watershed in preparation for future studies. The study indicates, that the order of the various land-uses according to biomass density is as follows: residual forest (567.19 Mg/ ha) < reforestation site (305.37 Mg/ha)>plantation (156.54 Mg/ha) > agroforestry (75.78 Mg/ha)> grassland (33.71 Mg/ha). The proportion of below ground biomass (BGB) to above ground biomass (AGB) is 22.18% is residual forests, 20.795% in a agroforestry, 20.03% in mixed reforestation, 19.49% in plantation, and 13.61% in grasslands. On the average, the BGB is around 19.22% of the total weight AGB. The carbon density in the watershed ranged from 99.33 MgC/ha to almost 290 MgC/ha, in the following order: residual forest (288.196MgC/ha)>mixed species reforestation (181.45 MgC/ha) > plantation (141.62 Mg/Cha)> grassland (110.36 MgC/ha)> agroforestry (99.33 MgC/ha). The percent of soil carbon in the total carbon of each ecosystem are 11.44, 24.27, 50.26, 87.78 and 64.6%, respectively. The study highlights the potential of the watershed for carbon sequestration and storage.